2023
DOI: 10.3389/fnut.2023.1215873
|View full text |Cite
|
Sign up to set email alerts
|

A review on anti-nutritional factors: unraveling the natural gateways to human health

Rehana Salim,
Iqra Bashir Nehvi,
Rakeeb Ahmad Mir
et al.

Abstract: Humans are constantly facing multiple health challenges from both communicable and non-communicable diseases that significantly affect their health. Additionally, drug resistance or failure has made the situation even worse and poses serious challenges for researchers to develop new drugs. Hence, to address these problems, there is an urgent need to discover and develop timely and long-term-based therapeutic treatments from different sources. One such approach is harnessing the potential of plant secondary met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 179 publications
0
3
0
Order By: Relevance
“…Many plant sources of protein contain antinutritional factors such as trypsin inhibitors, β-mannans, and glucosinolates, which reduce amino acid digestibility [52]. Some examples of plants that produce these antinutritional factors are soybean, quinoa, almonds, pomegranate, wheat, green tea, and cabbage [53]. One in vitro study of the digestibility of plant proteins compared to milk protein showed that the digestion of legume protein isolates, except for soybean, was similar to that found for milk proteins [51].…”
Section: Plant Proteinmentioning
confidence: 99%
“…Many plant sources of protein contain antinutritional factors such as trypsin inhibitors, β-mannans, and glucosinolates, which reduce amino acid digestibility [52]. Some examples of plants that produce these antinutritional factors are soybean, quinoa, almonds, pomegranate, wheat, green tea, and cabbage [53]. One in vitro study of the digestibility of plant proteins compared to milk protein showed that the digestion of legume protein isolates, except for soybean, was similar to that found for milk proteins [51].…”
Section: Plant Proteinmentioning
confidence: 99%
“…As per the reports of the World Health Organization (WHO), human beings are paying most of their attention to the use of herbal medicines as they have the least side effects [ 90 , 91 ]. A huge number of medicinal plants are currently being investigated to explore natural products as the best alternative to unsafe drugs [ 92 , 93 , 94 ].…”
Section: Role Of Saffron Bioactive Compounds Against Human Diseasesmentioning
confidence: 99%
“…In daily life, the consumption of unprocessed and improperly processed KB products is very likely to cause food poisoning. As research on non-nutritional factors has advanced, studies have reported that many compounds found in lower concentrations, often referred to as plant bioactive components or anti-nutritional factors, can have beneficial effects in preventing coronary atherosclerotic disease and various cancers [12][13][14]. The existence of non-nutritional factors such as toxic proteins and toxic alkaloids reduces the nutrient absorption rate of KBs and KB products, affecting the health of humans and animals [15].…”
Section: Introductionmentioning
confidence: 99%